Fostering English Language Skills’ Literacy Through Debate: Students' Views - Islamiah, Neneng; Fadila, Nur Ahyana (Cipta Pustaka Nusantara, 2024)
Education greatly influences the outcome of the students' learning process. One obstacle in education today concerns the literacy of students’ English language skills, namely listening, speaking, reading, and writing skills. Most students possess a low interest in enhancing the literacy of those four skills. The researchers believe that the strategy that can be adopted to enhance students’ literacy skills is the use of debate. So, the purpose of this research is to identify the students’ views of debate as a strategy to enhance English language skills’ literacy. Since the research used qualitative design, the researchers conducted semi-structured interviews, and used primary data and secondary data for data collection. The participants involved are debaters from different public and private universities in South Kalimantan. The result of the research showed that all participants agree that their literacy skills are influenced positively by debate and most participants view that debate can be used as a strategy to enhance the four skills’ literacy.